Prototype of Smart Door Using RFID Technology with Internet of Things (IoT) - Dyo Yulianto Wijaya; Andik Yulianto (Universitas Internasional Batam, 2021)
COVID-19 is a pandemic that can spread through the air or the surface of objects used in public facilities. One of the most vulnerable media in the spread of COVID-19 is the door. The use of conventional door locks and handles can be a source of transmission of COVID-19, considering that many people touch the surface of these objects. Based on this, the authors designed a smart door prototype using RFID as a key substitute. By using RFID, direct door contact can be minimized. In addition, the RFID reader will be connected to the internet, so that access to the door can be monitored via a web page